2022
DOI: 10.3389/fpsyt.2022.906234
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Needs in Mental Healthcare: Study Protocol of a Prospective Analytic Observational Study Assessing Nutritional Status, Eating Behavior and Barriers to Healthy Eating in Psychiatric Inpatients and Outpatients Compared to Healthy Adults

Abstract: BackgroundMental disorders are often associated with unhealthy eating behaviors and metabolic comorbidities. This can result in reduced life expectancy and poorer quality of life in people with mental disorders. This study protocol describes an observational study that examines the nutritional status and eating behaviors of people with severe mental illness (SMI) and the need for psychiatric treatment who were between 18 and 65 years old. In addition, the study focuses on possible barriers for healthy eating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In 13.8% of the patients, obesity with nutritional deficiency according to CONUT score was found, which emphasizes the importance to characterize the different nutritional profiles of these patients according to their nutritional status. 29,30 This might allow clinicians to develop adequate nutritional risk screening tools considering specificity of this population 10,11,31 and determined approaches for different clinical situations. 32,33 According to our findings, clinicians should include nutritional status-related analytical parameters for a global assessment of the nutritional status, and to consider them as factors that might influence the organic and mental well-being of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 13.8% of the patients, obesity with nutritional deficiency according to CONUT score was found, which emphasizes the importance to characterize the different nutritional profiles of these patients according to their nutritional status. 29,30 This might allow clinicians to develop adequate nutritional risk screening tools considering specificity of this population 10,11,31 and determined approaches for different clinical situations. 32,33 According to our findings, clinicians should include nutritional status-related analytical parameters for a global assessment of the nutritional status, and to consider them as factors that might influence the organic and mental well-being of patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another limitation is the lack of malnutrition risk screening tools for people with mental disorders. 10 However, there is an increasing interest to study the nutritional status in patients with severe mental disorders, 11,12 given the important burden that diet, lifestyle factors, and their consequences, may have in this population where physical health is often compromised, presenting a higher prevalence of cardiovascular diseases and a reduced life expectancy compared to the general population. 6,13,14 So far, various studies have reported nutritional status as a prognostic marker in a number of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This study was based on cross-sectional interview data and anthropometric measurements related to the assessment of the nutritional status and risk of malnutrition in people with SMI and the need for psychiatric treatment. The full prospective observational study was described in a previously published study protocol [21]. In total, 132 psychiatric patients, including 65 inpatients (Sample 1) and 67 outpatients (Sample 2), were interviewed at the beginning of their treatment at the Psychiatric Hospital of the University of Zurich (Psychiatrische Universitaetsklinik Zuerich [PUK]) in Switzerland.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews were conducted on average 14 days after the participants' admissions. The whole interview, as described in the study protocol [21], lasted for an average of 1 hour, while this study included only some of the questions. The participants were offered a drink, and they were allowed to take breaks according to their preferences and mental conditions.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation